(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article analyzes the agrotechnology of cultivation, biochemical composition, and prospects for the industrial processing of medicinal and nutritionally valuable Balkhi (white mulberry) and Shotut (black mulberry) fruits grown under the climatic conditions of Uzbekistan during seasonal vegetation periods. In addition, based on the data presented in the article, a comparative study was conducted on the chemical composition of the fruits, particularly focusing on the content of dry and soluble substances, natural sugars, organic acids, and mineral elements. Furthermore, relying on the scientific heritage of the great physician Abu Ali ibn Sina (Avicenna), the medicinal properties of these fruits and their potential use in food technology for producing dietary and traditional natural products such as mulberry syrup, juice, vinegar, raisins, and talqon were highlighted. The study also scientifically substantiates the high polyploid characteristics of Shotut and its practical significance in the confectionery, juice, and winemaking industries, especially as a source of natural food coloring agents and antioxidants.